Production of wild‐type and peptide fusion cutinases by recombinant Saccharomyces cerevisiae MM01 strains - Calado, Cecília (2020)
This study focused on the growth of Saccha‐romyces cerevisiae MM01 recombinant strains and the respective production of three extracellular heterologous cutinases: a wild‐type cutinase and two cutinases in which the primary structure was fused with the peptides (WP)2 and (WP)4, respectively. Different cultivation and strategies were tested in a 2‐L shake flask and a 5‐L bioreactor, and the respective cell growth and cutinase production were analyzed and compared for the three yeast strains. The highest cutinase productions and productivities were obtained in the fed‐batch culture, where wild‐type cutinase was secreted up to a level of cutinase activity per dry cell weight (specific cell activity) of 4.1 Umg−1 with activity per protein broth (specific activity) of 266 Umg−1, whereas cutinase‐(WP)2 was secreted with a specific cell activity of 2.1 Umg−1 with a specific activity of 200 Umg−1, and cutinase‐(WP)4 with a specific cell activity of 0.7 Umg−1 with a specific activity of 15 Umg−1. The results indicate that the fusion of hydrophobic peptides to cutinase that changes the physical properties of the fused protein limits cutinase secretion and subsequently leads to a lower plasmid stability and lower yeast cell growth. These effects were observed under different cultivation conditions (shake flask and bioreactor) and cultivation strategies (batch culture versus fed‐batch culture).